2016
DOI: 10.1134/s102279541611017x
|View full text |Cite
|
Sign up to set email alerts
|

Induced expression of Serratia marcescens ribonuclease III gene in transgenic Nicotiana tabacum L. cv. SR1 tobacco plants

Abstract: Transgenic Nicotiana tabacum L. cv. SR1 plants, characterized by an increase in the level of dsRNA-specific hydrolytic activity after induction by wounding, were obtained. The Solanum lycopersicum anionic peroxidase gene promoter (new for plant genetic engineering) was for the first time used for the induced expression of the target Serratia marcescens RNase III gene. Upon infection with the tobacco mosaic virus (TMV), the transgenic plants of the obtained lines did not differ significantly from the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…For example, transgenic tobacco plants producing barnase were shown to be protected from the late blight disease [71]. It has been found that potato plants expressing S. marcescens nuclease display enhanced resistance to pathogens [71,72]. Thus, genetic transformation using a bacterial RNase gene may be a promising approach for the engineering of plants with resistance to viral infection [73,74].…”
Section: Bacterial Nucleases and Their Antiviral Activitymentioning
confidence: 99%
“…For example, transgenic tobacco plants producing barnase were shown to be protected from the late blight disease [71]. It has been found that potato plants expressing S. marcescens nuclease display enhanced resistance to pathogens [71,72]. Thus, genetic transformation using a bacterial RNase gene may be a promising approach for the engineering of plants with resistance to viral infection [73,74].…”
Section: Bacterial Nucleases and Their Antiviral Activitymentioning
confidence: 99%
“…A crosstalk between responses to different stresses exists and plants carrying genes from certain pathogens were shown to display resistance towards other pathogens, such as bacterium vs. virus and yeast vs. virus (Cao et al, 2013;Zhirnov et al, 2016;Yang et al, 2019). Given that plant disease management is continuously evolving and that the presence of viruses in plants can also have beneficial outcomes (Gorovits et al, 2022), we investigated if the presence of viruses or the expression of viral proteins in plants may be beneficial against other pathogen infections.…”
Section: Introductionmentioning
confidence: 99%
“…Выдающийся организатор генетической науки в Сибири академик Владимир Константинович Шумный, в разные годы -директор Института цитологии и генетики СО РАН, председатель Объединенного ученого совета СО РАН по биологическим наукам, президент Вавиловского общества генетиков и селекционеров -известен в первую очередь как специалист в области генетики культурных растений, работы которого направлены на внедрение передовых методов генетики в селекционную практику. Под его руководством в Институте цитологии и генетики СО РАН активное развитие получили направления работ по генетике, хромосомной (Numerova et al, 2004;1985;Silkova et al, 2006), генной и геномной инженерии растений (Gerasimova et al, 2010;Ibragimova et al, 2015;Kochetov et al, 2004;Korotkova et al, 2017;Rivkin et al, 1993;Sangaev et al, 2007;Smirnova et al, 2019;Trifonova et al, 2004;Turchinovich et al, 2004;Zagorskaya et al, 2009;Zhirnov et al, 2016). Особое внимание в его работах уделено отдаленной гибридизации растений и полиплоидии (Adonina et al, 2011;Leonova et al, 2013;Orlovskaya et al, 2015;Shumny et al, 2016;Shumny, Pershina, 1979;1980;Silkova et al, 2011;2012;Svitashev et al, 1995), а также гетерозису растений и связанным с этим вопросам (инбридинг, генетико-селекционные аспекты опыления растений и так далее) (Kovalenko, Shumny, 2008;Pokhmel'nykh, Shumny, 1999;Shumny et al, 1978).…”
unclassified